Production of heterologous Providencia rettgeri penicillin acylase in Escherichia coli - Chou, C. P.; Lin, M. I.; Wang, W. C. (Journal of the Chinese Institute of Chemical Engineers, 2000)
In this work, we constructed several expression plasmids for the production of Providencia rettgeri penicillin acylase (EC 3.5.1.11; PAC) in Escherichia coli. DNA fragments containing the pac gene from P. rettgeri ATCC31052 were PCR-amplified and cloned in to the expression vectors so that the pac gene expression was controlled by the tac or trc promoter system. The effects of culture conditions, such as IPTG concentration, temperature, and carbon source, on the native or heterologous expression were investigated. Among a selection of expression systems, JM109 harboring pUTKnPAC2601 gave the highest PAC activity and could be of interest for industrial application. Cultivation should be performed at a temperature ranging from 28 degrees C to 33 degrees C and the medium could be supplemented with glycerol. The host/vector system offers an opportunity for high-temperature-oriented PAC production, which is usually conducted at a low temperature. Volumetric PAC activity at more than fiftyfold (similar to 820 U/L) that of the native expression in ATCC31052 (similar to 15 U/L) could be reached by optimization of the host/vector system and culture conditions.